Social Enterprise and Urban Regeneration: A Model for the Future? - Carpenter, Juliet (Calitatea Vieții, 2013)
The UK is currently experiencing the longest and deepest recession since the 1920s. Against this backdrop, social enterprise is increasingly been seen by policy makers as playing an important role in boosting the local economy, as an alternative way of promoting economic development and contributing to regeneration. This paper examines the links between social enterprise and regeneration, and then explores these issues through a case study where social enterprise has been embedded within a regeneration strategy. The paper shows that there is real potential for social enterprise to play a role in future regeneration schemes, developing from the bottom up, in community-led initiatives. However, social enterprise is only one potential solution to the deep-seated challenges that underpin deprived neighbourhoods. These should be addressed through a wider holistic strategy to create more sustainable and socially just communities.